Experimental study of rock wool on the farmland soil erosion and crop growth of winter wheat and its comprehensive evaluation - Li, Wei; Liu, Shanshan; Wang, Yicheng; Qin, Tianling; Zhang, Xin; Li, Chenhao; Feng, Jianming (Frontiers in Environmental Science, 2023)
Droughts and flooding occur frequently due to climate change and human activities, which have significantly affected the ecological environment of farmland and crop production. To dissolve the above problem and explore the effect of the Porous Fiber Material (PFM, rock wool) on the winter wheat farmland’s ecological environment, we set 24 artificial rainfall experiments to analyze the impact of PFM on the farmland runoff, Soil Water Storage Capacity (SWSC), nitrogen and phosphorus loss and crop growth. Finally, the Entropy-Critic comprehensive evaluation method was used to select the best solution for PFM embedding. The result shows that PFM could reduce the runoff by 49.6%-93.3%, and it made the SWSC increase by 0.2%-11% Vol in the 10 70cm depth. During the runoff process, the concentration of nitrogen and phosphorus decreased with the increase of the PFM volume, while the nitrogen and phosphorus loss reduced by 51.9%-96.6% and 72.4%-96.4% respectively when PFM was buried in the farmland, so PFM could effectively promote soil and water conservation. Finally, PFM increased the biomass and yield by a maximum of 12.1% and 20.4% respectively due to the large retention of water and nutrients. However, when the volume of PFM embedding was too large, PFM easily caused insufficient water storage in short-duration rainfall or irrigation, which made the PFM unable to release water to alleviate the soil water deficit during the critical growth period, which may result in drought events being aggravated and crop yield reduced. Therefore, combined with the above experimental results and based on the comprehensive evaluation method, this study indicates that PFM could obtain the best comprehensive benefit in the embedding volume of 536.73 m3/ ha. Overall, this study is conducive to clarifying the comprehensive application effect of PFM in agricultural production, pollution control, and urban landscape, and it provides an important basis for expanding its application field and promoting the stability of farmland ecosystems.